Manajemen Kompetensi Profesional Guru Akidah Akhlak di Madrasah Aliyah Al-Ikhsan Beji Kedungbanteng - Nurfuadi Nurfuadi (Journal on Education, 2023)
Competence for several professions is an important requirement in carrying out the framework and goals of the organization. The purpose of this study was to analyze how the management of the professional competence of the Aqidah Akhlak teachers at Madrasah Aliyah Al-Ikhsan Beji Kedungbanteng. This research is qualitative with the results of the study namely in the implementation of Islamic Religious Education teacher competency management for developing the quality of learning at Madrasah Aliyah Al-Ikhsan Beji Kedungbanteng, namely for the Aqidah Akhlak subject when in class 10 the teacher explained Aqidah Akhlak and Fiqh material, after explaining the material then opened a question and answer session, after that there was a clarification from the teacher. For the 11th grade learning model, first the students and the teacher enter and then pray together, then the teacher opens with a greeting after that the teacher appoints one of the student groups to present the results of the group discussion which at the previous meeting had already been formed. Of the 35 students who have made discussion groups into 7 groups with each group there are approximately 5 students. In each one group of 5 students the tasks were divided to facilitate the discussion including for each task, namely there was a moderator, note taker, and presenter. After presenting the results of the discussion, a question and answer session was opened with several models of questions.